The world experience of implementing processes of industrialization - Dulambaeva, Kaliyeva, R., A. T., Ye. (Journal of Economic Research & Business Administration, 2016)
In modern conditions, industrialization is a process of characterizing the level of development of the productive forces, the state and the quality of the institutional framework of the country. Formation of the industrial sector is an objective process in the development of social production. The main feature of the industrialization of the country is a departure from the old, traditional way of production (with a predominance of raw growth factor). These processes are objective today in many developed countries. This article discusses the different approaches to the implementation of these processes in the world. An an overview models of industrial policy, which have been tested in various countries: export-oriented, import-substitution model, innovative model. In addition with the existing features in the implementation process of industrial-innovative development of defined common component – the active role of the state.